Uveitis model in rabbit: Dexamethasone loaded PHBSA nanoparticles - Erdal, Ebru; Batur, Baris; Ugurlu, Nagihan; Cetin, Esin Akbay; Turkoglu, Nelisa Lacin; Cakal, Cafer; Demirbilek, Murat (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2026)
The study aims to investigate the efficacy and safety of intravitreal dexamethasone-loaded polyhydroxybutyratestearic acid blend nanoparticles (PHBSA) in treating experimental uveitis. Dexamethasone (DEX) loaded PHBSA nanoparticles were fabricated. An experimental autoimmune uveitis model was established in rabbits and administered the nanoparticles. Fundus fluorescence photometry (FFM), optical coherence tomography (OCT), and fundus examinations were conducted to assess the treatment's effectiveness. Additionally, cytokine levels in the anterior chamber were measured. The uveitis rabbit model was successfully created by the intravitreal injection of 2 mu g of lipopolysaccharides (LPS). Following the administration of the DEX-loaded PHBSA nano-particles, clinical evaluations revealed significant therapeutic effects in both OCT and FFM measurements. A noteworthy change was also observed in the intraocular pressure (IOP) readings. The results indicated a decrease in the clinical signs of uveitis after administering the dexamethasone-loaded nanoparticles, accompanied by a reduction in pro-inflammatory cytokines. These findings suggest that dexamethasone-loaded nanoparticles may serve as a potential treatment for uveitis.
Keywords: PHBSA nanoparticles; Dexamethasone; Uveitis; Reduce injection frequency; ENDOTOXIN-INDUCED UVEITIS; OCULAR IMMUNE PRIVILEGE; CYTOKINE PROFILE; Ophthalmology